Bioactive Polyphenols from Southern Chile Seaweed as Inhibitors of Enzymes for Starch Digestion - Veronica Pacheco, Luz; Parada, Javier; Ricardo Perez-Correa, Jose; Salome Mariotti-Celis, Maria; Erpel, Fernanda; Zambrano, Angara; Palacios, Mauricio (My University, 2020)
The increment of non-communicable chronic diseases is a constant concern worldwide, with type-2 diabetes mellitus being one of the most common illnesses. A mechanism to avoid diabetes-related hyperglycemia is to reduce food digestion/absorption by using anti-enzymatic (functional) ingredients. This research explored the potential of six common Chilean seaweeds to obtain anti-hyperglycemic polyphenol extracts, based on their capacity to inhibit key enzymes related with starch digestion. Ethanol/water hot pressurized liquid extraction (HPLE), which is an environmentally friendly method, was studied and compared to conventional extraction with acetone. Total polyphenols (TP), antioxidant activity, cytotoxicity and inhibition capacity on alpha-glucosidase and alpha-amylase were analyzed. Results showed that theDurvillaea antarctica(cochayuyo) acetone extract had the highest TP content (6.7 +/- 0.7 mg gallic acid equivalents (GAE)/g dry seaweed), while its HPLE ethanol/water extract showed the highest antioxidant activity (680.1 +/- 11.6 mu mol E Trolox/g dry seaweed). No extract affected cell viability significantly. Only cochayuyo produced extracts having relevant anti-enzymatic capacity on both studied enzymes, showing a much stronger inhibition to alpha-glucosidase (even almost 100% at 1000 mu g/mL) than to alpha-amylase. In conclusion, from the Chilean seaweeds considered in this study, cochayuyo is the most suitable for developing functional ingredients to moderate postprandial glycemic response (starchy foods), since it showed a clear enzymatic inhibition capacity and selectivity.
Keywords: seaweed polyphenols; hypoglycemic effect; starch digestion; enzyme inhibition; cochayuyo